New Media, Profit Orientation, and Lifestyle among Indonesian Muslim Millennials: A Rational Choice Perspective on Capital Market Engagement - Henny Saraswati; Umi Kultsum; Ade Fakih Kurniawan (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article explores the interplay between new media, lifestyle aspirations, and financial behavior among Indonesian Muslim millennials in relation to capital market investments. Anchored in Rational Choice Theory (RCT), the study investigates how economic motivations, religious considerations, and social influences shape investment decisions. Drawing on qualitative data collected through in-depth interviews with more than 20 millennial Muslims from Yogyakarta and East Java, the study reveals a dynamic shift in perception—from viewing investment as a prestigious lifestyle marker to embracing it as a rational strategy for long-term financial security. Social media and smartphone technology emerge as key facilitators of financial literacy and access, enabling individuals to engage with the capital market despite limited formal financial education. Moreover, the research highlights how religious legitimation, particularly the fatwa from Indonesia’s National Sharia Council (DSN MUI), contributes to the perceived permissibility of stock market participation among observant Muslims. However, this perception is not universally acknowledged, indicating a nuanced negotiation between religious norms and market behavior. The findings suggest that capital market participation among Muslim millennials is not solely driven by profit-seeking behavior but also deeply influenced by peer dynamics, lifestyle aspirations, and broader socio-religious frameworks. This study contributes to a growing body of literature on Islamic financial practices, digital religiosity, and the socio-cultural dimensions of economic life in Muslim-majority societies.